Hypothesis: improving literacy about health workforce will improve rural health workforce recruitment, retention and capability - Alexandra Martiniuk; Richard Colbran; Robyn Ramsden; Dave Karlson; Emer O'Callaghan; Estrella Lowe; Michael Edwards; Sharif Bagnulo; Imogene Rothnie; Laura Hardaker; Bernadette Gotch; Arna Wotherspoon (BMC, 2019)
Abstract Background One of the key barriers to health in rural areas is health workforce. Poor understanding and communication about health workforce across all stakeholder groups (including the broad community) is very common and can negatively affect the health workforce, recruitment, experiences and outcomes. Hypothesis In this paper, we propose the concept of literacy about health workforce. We propose this as a specific, actionable extension of the existing and well accepted health literacy concept. We hypothesise that improving literacy about health workforce will improve, in particular, rural health workforce recruitment, retention and capability. Implications of the hypothesis We propose that literacy about health workforce is important for all members of the health and broader system (e.g. local GP, mayor, workforce agency, health manager, Aboriginal health worker, carers, community health facilitators, patients, schools, local businesses, cultural and recreation groups) because we hypothesise their literacy about health workforce affects their capacity to make informed decisions and take action to manage their health workforce needs in direct synchrony with the community's health needs. We hypothesise that improving literacy about health workforce will improve the effectiveness and efficiency of attracting, recruiting, training, and retaining a high quality, capable, health workforce, and further, will support the development and acceptance of innovative solutions to health workforce crises such as new models of care. This hypothesis is action orientated, is testable and includes the consideration of methods to engage and improve literacy of those within and external to the health workforce.